Accomplishing Masculinity through Anti-Lesbian, Gay, Bisexual, and Transgender Homicide: A Comparative Case Study Approach. (April 2015) - Kelley, Kristin; Gruenewald, Jeff
In the current study, we seek to understand the dynamic processes of fatal attacks against lesbian, gay, bisexual, and transgender (LGBT) individuals across different situational circumstances. A review of prior research and story line analyses of 121 anti-LGBT homicides led to the creation of a homicide typology based on offender mode of victim selection. Guided by symbolic interactionism and theories of masculinity and violence, five representative case studies are conducted based on various open-source materials. The purpose of the case studies is to examine the applicability of theories of masculinity and violence for explaining anti-LGBT homicides across different modes of victim selection. We conclude that interactionist and masculinity theories of violence can in part illuminate how and why offenders use violence to demonstrate masculinity in some anti-LGBT homicide scenarios.